Analysis of Behaviour for Bolt Joint of Corrugated Plate Subjected to Bending Moment. Issue 5 (June 2020) - Guo, Qi; Wu, Meng; Pu, Guangning; Guo, Kun
Abstract: In this paper, the stress distribution of corrugated plate and bolt is obtained by numerical simulation of single row screw connection of corrugated plate with different side distance. The position of rotation axis and suitable side distance of single row bolt under the action of moment are determined, and the calculation formula of single row bolt connection of corrugated plate under the action of moment is given by referring to the calculation formula of steel structure bolt connection.